Analisis Kasus Wanprestasi Antara Debitur Dan Kreditur Terhadap Perjanjian Pinjaman Kredit Bank Studi Kasus Putusan (Nomor 5/PDT.G.S/2023/PN.BTG) - Trianda Lestari; Syahrando Muhti; Muhamad Fatur Rahman Bey Husdi (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
A broken promise or default is a situation where a debtor is unable to fulfill his obligations in accordance with the debt and receivable agreement he made, for example not making installments or repayment on time. As in article 13138 of the Civil Code which states "All agreements made in accordance with law apply as law for those who make them. This agreement cannot be withdrawn other than by agreement of both parties, or for reasons determined by law, the agreement must be carried out in good faith. In this paper, the problem is regarding the bank credit payment agreement made between the debtor and the creditor in the contents of the agreement that has been given by agreement between the parties given a period of time by the creditor to the debtor, but the debtor is negligent and does not pay compensation even though it has been billed and a summons has been given. or a warning, so that the debtor files a lawsuit. The theory in this research uses contract law theory which regulates agreements and methods using normative legal research methods which refer to court decisions and statutory regulations. So the title that the researcher will discuss is the analysis of cases of default between debtors and creditors regarding bank credit loan agreements, case study decision number 51/PDT.G.S/2023/PN.BTG